Flutuação populacional de cigarrinhas-das-pastagens na Região Oeste do Paraná - Lohmann, Tiago Rodrigo [UNESP] (2010)
The spittlebugs are considered the most important pests in tropical pastures. The damages caused by these insects decrease the production of pastures. The objective this work was to study the population dynamics of Notozulia entreriana, from June 2007 to June 2008, and the correlation with meteorological and environmental factors (rainfall, temperature, daily solar radiation and pasture height). Therefore, sampled were made in three areas of grassland in the municipality of Marechal Candido Rondon-PR. Sampling of adults and nymphs was made. Also we determined which species of spittlebugs (Hemiptera: Cercopidae) occur in the western region of Parana State. The population fluctuation of N. entreriana showed four peaks during the period of favorable development - spring / summer. The daily solar radiation had a higher correlation with the population. Rainfall, temperature and pasture height had little correlation with the population dynamics. The species that occurred with greater abundance was N. entreriana, representing 88.4% of the total insects collected in western of Parana State.